Is low-dose dextrose prolotherapy as effective as high-dose dextrose prolotherapy in the treatment of lateral epicondylitis? A double-blind, ultrasound guided, randomized controlled study - OKÇU, MEHMET (My University, 2022)
© 2022 American Congress of Rehabilitation MedicineObjectives: To investigate the effects of prolotherapy (PrT) on pain, functionality, clinical improvement and to compare the 5% low and 15% high dose dextrose PrT in chronic lateral epicondylitis. Design: A double-blind, parallel groups, randomized controlled study. Settings: Outpatient Clinic. Participants: Sixty patients (N=60), aged 44.30±10.31 years old, with chronic lateral epicondylitis were allocated randomly into 3 groups. Interventions: To Group 1 5% dextrose PrT, to Group 2 15% dextrose PrT, to Group 3 0.9% saline injections were done at 3 times (weeks 0, 3, 6), to the entheses of forearm extensors and annular ligament. Main Outcome Measures: The primary outcomes were handgrip strength, visual analog scale-rest (VAS-R), visual analog scale-activity (VAS-A), pressure-pain threshold, and Quick Disability of the Arm, Shoulder and Hand (Q-DASH). The secondary outcomes were clinical improvement (Disease Global Assessment Questionnaire), side effects, and complications. Primary outcomes were collected at baseline week 0, week 3, and 12. Secondary outcomes were collected at weeks 3 and 12. Results: In Group 2, VAS-A and VAS-R (at week 3), handgrip strength and pressure-pain threshold (at week 12) were significantly different than other groups (P.05). Conclusion: In chronic lateral epicondylitis, 5% and 15% dextrose PrT is more effective in pain, handgrip strength, functionality, and clinical improvement than %0.9 saline. There was no difference in functionality, clinical improvement, side effects, and complications between the PrT groups. 15% dextrose PrT was more effective in handgrip strength and pressure-pain threshold at week 12 and pain at week 3. We recommend 15% dextrose PrT based on this study.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Lateral epicondylitis; Prolotherapy; Tendinopathy